A linear wave propagation‐based simulation model for dense and polarized crowds. (8th November 2020) - Chen, Qiang; Luo, Guoliang; Tong, Yang; Jin, Xiaogang; Deng, Zhigang
Abstract: Fluid‐like motion and linear wave propagation behavior will emerge when we impose boundary constraints and polarized conditions on crowds. To this end, we present a Lagrangian hydrodynamics method to simulate the fluid‐like motion of crowd and a triggering approach to generate the linear stop‐and‐go wave behavior. Specifically, we impose a self‐propulsion force on the leading agents of the crowd to push the crowd to move forward and introduce a Smoothed Particle Hydrodynamics‐based model to simulate the dynamics of dense crowds. Besides, we present a motion signal propagation approach to trigger the rest of the crowd so that they respond to the immediate leaders linearly, which can lead to the linear stop‐and‐go wave effect of the fluid‐like motion for the crowd. Our experiments demonstrate that our model can simulate large‐scale dense crowds with linear wave propagation.